Proteome and Peptidome of Vipera berus berus Venom - Aleksandra Bocian; Małgorzata Urbanik; Konrad Hus; Andrzej Łyskowski; Vladimír Petrilla; Zuzana Andrejčáková; Monika Petrillová; Jaroslav Legath (Molecules, 2016)
Snake venom is a rich source of peptides and proteins with a wide range of actions. Many of the venom components are currently being tested for their usefulness in the treatment of many diseases ranging from neurological and cardiovascular to cancer. It is also important to constantly search for new proteins and peptides with properties not yet described. The venom of Vipera berus berus has hemolytic, proteolytic and cytotoxic properties, but its exact composition and the factors responsible for these properties are not known. Therefore, an attempt was made to identify proteins and peptides derived from this species venom by using high resolution two-dimensional electrophoresis and MALDI ToF/ToF mass spectrometry. A total of 11 protein classes have been identified mainly proteases but also l-amino acid oxidases, C-type lectin like proteins, cysteine-rich venom proteins and phospholipases A2 and 4 peptides of molecular weight less than 1500 Da. Most of the identified proteins are responsible for the highly hemotoxic properties of the venom. Presence of venom phospholipases A2 and l-amino acid oxidases cause moderate neuro-, myo- and cytotoxicity. All successfully identified peptides belong to the bradykinin-potentiating peptides family. The mass spectrometry data are available via ProteomeXchange with identifier PXD004958.